PERLINDUNGAN HUKUM PASIEN TERHADAP PRAKTIK KONSULTASI ONLINE DOKTER PADA APLIKASI HALODOC - YUHANNA YUHANNA; Muhammad Irfan (Private Law, 2023)
The purpose of this study is to analyze the patient's legal protection for online doctor consultation practices on the Halodoc application and to analyze the doctor's legal responsibility if the patient suffers a loss of health. This research is a normative legal research method with the statute approaches, the conceptual approaches, and the comparative approaches. The result of the study is the patient's legal protection against online doctor consultation in the Halodoc application by preventive legal protection in the informed consent, medical records, and repressive legal protection by giving sanctions and lawsuits for compensation against doctors who make mistakes or malpractices. Doctors' legal responsibilities in the Halodoc application are categorized into three types of legal responsibility, namely responsibility in the areas of civil law, criminal law, and administrative law.